Human Papillomavirus Vaccination in Georgia: Evaluating the Georgia HPV Work Group - King, Adrian R. (J Community Health, 2019)
HPV-related cancers can be prevented through HPV vaccination, however uptake and completion of the vaccination in the state of Georgia remains suboptimal. The research team conducted two online focus groups with members of the Georgia Cancer Control Consortium HPV Work Group in efforts to better understand the role that the working group could have on increasing vaccination uptake and completion in the state of Georgia. Analysis of the focus groups was completed using a Grounded Theory approach. Various aspects of the Working Group were discussed throughout the focus groups with a number of key points for growth identified both by the participants during the discussion, and by the research team during analysis. Predominantly, a primary point for growth of the Working Group lies in building its capacity to collectively conduct HPV vaccination-related activities. An online webportal specifically designed for the Working Group was identified as a tool for improving Working Group communication, sharing best practices and resources, and to collectively develop activities, research projects, and HPV vaccine promotion events in a culturally competent and age appropriate manner in efforts to improve vaccine uptake and completion throughout the state of Georgia.